2022
DOI: 10.1002/brb3.2560
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical cognitive status in patients with low‐grade glioma and epilepsy: Testing the effects of seizures, antiseizure medications, and tumor localization

Abstract: Background: Low-grade gliomas (LGGs) are frequently associated with epilepsy. There are few studies addressing the impact of seizures, antiseizure medications (ASMs), and lesion localization on presurgery cognitive functioning. Methods:We tested the relation between the above-mentioned variables in a continuous series of 73 young patients (mean age 38.3 years ± 11.7) affected by LGGs and epilepsy. The anatomical areas, involved in this sample, were the left insula with surrounding cortical and subcortical area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Tumor volume was associated with effect on preoperative cognitive function in patients with LGG, including insula, as quantified by standard MRI sequences and voxel-based lesion symptom mapping (VLSM) The study consisted of 8 patients with dominant hemisphere insular glioma, and they demonstrated significantly poor performance in object naming. Additionally, VLSM revealed that for both left and right hemispheric glioma groups, 36% of patients with working memory (verbal and visual) impairment had insular involvement ( Guarracino et al, 2022 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…Tumor volume was associated with effect on preoperative cognitive function in patients with LGG, including insula, as quantified by standard MRI sequences and voxel-based lesion symptom mapping (VLSM) The study consisted of 8 patients with dominant hemisphere insular glioma, and they demonstrated significantly poor performance in object naming. Additionally, VLSM revealed that for both left and right hemispheric glioma groups, 36% of patients with working memory (verbal and visual) impairment had insular involvement ( Guarracino et al, 2022 ).…”
Section: Future Directionsmentioning
confidence: 99%